Dealing With Snakes in Florida's Residential Areas - Introduction - Steve A. Johnson; Monica E. McGarrity (EDIS)
This document is WEC 219, the first in a 4-part series entitled Dealing with Snakes in Florida's Residential Areas, by Steve A. Johnson and Monica E. McGarrity that provides information on how to identify snakes that are commonly encountered in residential settings in Florida, how to prevent negative encounters, and how to respond in the unlikely event that someone is bitten by a snake. Published by the UF Department of Wildlife Ecology and Conservation, July 2007.